Clinical significance of elevated liver transaminases in HIV-infected patients. (1st July 2019) - Cai, Jia; Osikowicz, Maria; Sebastiani, Giada
Abstract : N/A: Elevation of liver transaminases is common in patients infected with the HIV. Although this is usually an incidental finding during regular work-up, HIV-infected patients with transaminase elevations require additional visits for laboratory studies and clinical assessments, and often undergo interruptions and changes in antiretroviral therapy (ART). Alanine aminotransferase is present primarily in the liver, thus being a surrogate marker of hepatocellular injury. Aspartate aminotransferase is present in the liver and other organs, namely cardiac and skeletal muscle, kidney and brain. Serum levels of both liver transaminases predict liver-related mortality. Moreover, serum fibrosis biomarkers based on alanine aminotransferase and aspartate aminotransferase predict all-cause mortality. In a busy clinical setting, a diagnostic approach to elevated liver transaminases could be complicated given the frequency and nonspecificity of this finding. Indeed, HIV-infected individuals present multiple risk factors for liver damage and chronic elevation of transaminases, including coinfection with hepatitis B and C viruses, alcohol abuse, hepatotoxicity due to ART, HIV itself and frequent metabolic comorbidities leading to nonalcoholic fatty liver disease. This review provides an update on epidemiology of elevated liver transaminases, summarizes the main etiologic contributors and discusses the prognostic significance and a pragmatic approach to this frequent finding in the clinical practice of HIV medicine. With the aging of the HIV-infected population following the successful implementation of ART in Western countries, liver-related conditions are now a major comorbidity in this setting. As such, clinicians should be aware of the frequency, clinical significance and diagnostic approach to elevated liver transaminases.